The Effect of Postmenopausal Osteoporosis on Middle Ear Resonance Frequency - Baytaroglu, Berk; Jafarov, Sabuhi; Erbek, Selim Sermed (Journal of International Advanced Otology, 2021)
BACKGROUND: The effect of postmenopausal osteoporosis on the middle ear mechano-acoustic system is unknown. The aim of this study is to investigate whether or not middle ear resonance frequency is affected in females with postmenopausal osteoporosis. METHODS: The study included postmenopausal women aged 45-60 years, separated into 2 groups as females with postmenopausal osteoporosis and healthy postmenopausal females (control group). A detailed anamnesis was taken from all subjects and then the ear, nose, and throat examinations were done followed by pure tone audiometry, tympanometry, and multifrequency tympanometry tests. The groups were compared in respect of pure tone average, bone conduction threshold, RF, static admittance, and tympanometric peak pressure values. RESULTS: The mean age of the patients was 59.2 ± 4.53 years (range, 48-65 years) in the postmenopausal osteoporosis group and 57.11 ± 4.27 years (range, 48-65 years) in the control group (P > .05). The mean resonance frequency values for the postmenopausal osteoporosis and control group were 954.41 ± 127.47 and 935.29 ± 126.39 Hz (P > .05 ). The mean static admittance values for the postmenopausal osteoporosis and control group were 0.82 ± 0.33 and 0.85 ± 0.3 mmho, and mean tympanometric peak pressure values were −7.35 ± 18.52 and −6.94 ± 19.52 daPa (P > .05 for both static admittance and tympanometric peak pressure). The mean pure tone averagevalues for the postmenopausal osteoporosis and control group were 20.96 ± 6.82 and 15.60 ± 7.81 dB, and mean bone conduction threshold values were 17.57 ± 6.03 and 12.10 ± 6.52 dB (P < .05 for both pure tone average and bone conduction threshold). CONCLUSIONS: The results showed that the middle ear resonance frequency values were not affected in postmenopausal osteoporosis patients, but there was seen to be greater sensorineural hearing loss in females with postmenopausal osteoporosis compared to healthy postmenopausal females. Cite this article as: Baytaroglu B, Jafarov S, Erbek SS. The effect of postmenopausal osteoporosis on middle ear resonance frequency. J Int Adv Otol. 2021;17(6):526-529.